Archiwum kapituły i parafii Opatów - Rzepecka, Marta (Archiwa, Biblioteki i Muzea Kościelne, 2021)
The aim of the following article is to present and analyse the collection of the Chapter and Parish Archive in Opatów. The Opatów chapter, existing for over eight centuries, is one of the oldest Polish collegiate chapters. The canons of Opatów produced a great number of records, which constitute an important source for the regional history. Unfortunately, through the centuries the documents of this archive have been depleted due to numerous wars, partitions, church fires and because of borrowing of these documents. The author concentrates on the archival sources ffom the Chapter and Parish Archive in Opatów. Among others, there are statutes and detailed reports of the Opatów chapter meetings ffom the years 1762-1822 and 1848-1972, original documents issued for the chapter and its church sińce the 16® century, the records of the bishops of Sandomierz, consistory’s and diocesan curia’s correspondence, inventories of a church property and benefices of St Marcin Church in Opatów. This archive materiał includes, among other things, information on canons, the chapter, a church property and on the materiał and spiritual condition of the parishioners. The other collection (The Parish Archive in Opatów) holds mainly registers. There are birth, marriage, death records. The oldest records are baptism ones. They have been kept sińce the beginning of the 17® century. The oldest death records are ffom the end of the 17® century, while marriage ones ffom the first half of the 18® century. The registers are connected with the banns books of the intended marriages and prenuptial exams. In the above-mentioned collection there are such books ffom the 20® century. Apart ffom registers, interesting materiał to leam the history of the parish of Opatów can be found in petty cash ledgers and minutę books such ecclesiastical institutions as the Third Order of St Francis, Rosary Fratemity, rosary groups and "Caritas"